Peningkatan Kualitas Sumber Daya Manusia Di Era Disrupsi Dan Mahasiswa Menjadi Agen Perubahan - Fransiska, Jenny (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
Excellent human resources are a country's greatest asset, so that this nation can easily keep up with the rapid progress of this era. Furthermore, superior human resources reflect the successful management of educational institutions in a country. This study uses a literary reflection methodology, including exploration of sources such as journals, books, and online materials. In the era of disruption that we have today, the development of human resources plays a very important role. It is not only the government's responsibility to improve the quality of human resources; The role of students is also very important. As educated individuals, students have the ability to think critically and in-depth knowledge in various fields. The hope is that with the industrial revolution 4.0 towards Society 5.0, Indonesia can follow developments that suit the needs of modern society. In this case, the measure of a country's success or failure in facing change in this era of disruption is the welfare of the people in various fields, especially in education and the economy.